2017
DOI: 10.5380/biofix.v2i0.56343
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionamento E Classificação De Riscos Da Colheita Florestal Em Relevo Declivoso

Abstract: RESUMO ABSTRACTA busca pela redução dos custos de produção leva as empresas florestais à procura de terras economicamente mais acessíveis para implantar suas atividades, como as áreas com declividade acentuada. Os efeitos potenciais da declividade no dimensionamento e no agravamento de riscos na colheita florestal motivaram este estudo, classificando-os para as ações e ocupações envolvidas no corte e na extração florestal. A classificação considerou as diretrizes das Normas Regulamentadoras número 9, 15, 17 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…When comparing the values to the standards established by regulations, it is observed that there is no need for corrective or mitigation measures regarding thermal comfort for semi-Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.17, n.4, p. 01-27, 2024 mechanized cutting and manual extraction activities, like findings by Nascimento and Catai (2017). These results may be due to data collection occurring between the autumn and winter seasons, which significantly affects the average temperature and relative humidity (Dereczynski et al, 2019).…”
Section: Thermal Comfort (Tc)mentioning
confidence: 78%
“…When comparing the values to the standards established by regulations, it is observed that there is no need for corrective or mitigation measures regarding thermal comfort for semi-Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.17, n.4, p. 01-27, 2024 mechanized cutting and manual extraction activities, like findings by Nascimento and Catai (2017). These results may be due to data collection occurring between the autumn and winter seasons, which significantly affects the average temperature and relative humidity (Dereczynski et al, 2019).…”
Section: Thermal Comfort (Tc)mentioning
confidence: 78%
“…Regarding the use of machines and tools, the MIAR forest states that the severity depends on the type of machine or tool the worker uses when carrying out the activity. The severity levels were defined according to the bibliography on this subject specifically applied to native forest exploitation [4,8,[39][40][41][42][43][44][45][46][47]. In the valuation of this parameter, it was decided that the severity is higher if the activity is carried out with forestry machines such as, for example, a loader, a forest tractor, a tracked tractor or a logging truck.…”
Section: Machines and Tools Handling (Mt)mentioning
confidence: 99%
“…The MIAR forest states that severity is higher when work is carried out along a path with irregular terrain with a slope and obstacles to overcome and lower if the activity is carried out along a path on regular terrain with no slope and no obstacles to overcome. The severity levels of the occupational accident according to the characteristics of the path were defined according to specific bibliography on this topic, adapted to native forestry [8,[39][40][41][42][43][44][45][46]. In the valuation of this parameter, small bridges, such as a bush or a penguela, were considered obstacles of difficult transposition.…”
Section: Site Characteristics-terrain Slope (Ts) and Obstacles (Obst)mentioning
confidence: 99%
“…Os trabalhadores podem estar expostos a uma diversidade de possibilidades de acidentes oriundos dos mais variados riscos, tais como: ruído, vibração, calor, postura incômoda, levantamento manual de carga, queda, corte, poeira, gases, vapores, entre outros, originados por máquinas, organização de trabalho, condição do ambiente, ou até mesmo por fonte natural (ALMEIDA; ABRAHÃO; TERESO, 2015;CATAI, 2017;RODRIGUES;MEDEIROS, 2006;FLORIANI NETO;NASCIMENTO;MINETTE et al, 1998MINETTE et al, , 2007RIBEIRO, 2016;SANT'ANNA;MALINOVSKI, 2009;SCHETTINO et al, 2017;SOUZA et al, 2015).…”
Section: Revisão De Literaturaunclassified